The Implementation of Academic Supervision by School Principals in Developing the Professional Competence of Elementary School Teachers - Ahsanul Huda Santosa; Yenny Widyawati; Anam Sutopo; Sabar Narimo (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to describe the implementation of academic supervision by the principal in developing the professional competence of teachers at elementary school. This research uses a case study method. The subjects or respondents of this study are the principal and teachers of SDN 03 Wukirsawit, Jatiyoso, Karanganyar. The types of data include results from observations, interviews, and documentation. Data validity was ensured through source triangulation. The data analysis technique used is interactive analysis, which consists of data collection, data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that: (1) the principal has designed a systematic classroom observation program, including preparation, implementation, and discussion of observation results; (2) the implementation of supervision involves assessments through pre-observation, observation, and post-observation; (3) the results of the supervision are analyzed to identify the weaknesses and strengths of the teachers; (4) principles such as practicality, objectivity, cooperation, family-like atmosphere, democracy, comprehensiveness, and continuity have been applied by the principal.